Talking to One Another in Education: The Importance of Bildung and Tact - Gilham, Christopher (Disability Studies Quarterly, 2012)
This interpretive essay attempts to show how it is possible to be an educator with important things to say about good practice gained from experiences – a cultivation of oneself known as Bildung - that often happens "…beyond our wanting and doing"(Gadamer, 1975, p. xxvi). Such knowledge is often left unsaid or said in particular kinds of ways because there isn't a safe or open or accepting environment in which to talk about one's experiences unless such talk fits a predominant discourse (Foucault, 1977). What is revealed is the power of the discourse, as we hold it, intentionally or not, over the truths of what we gain in experience. In other words, unless our experiences as educators are verified through expert empirical knowledge, our words are simply 'mine' versus 'yours' with no place to dialogue in the sense Gadamer thought we needed to in order to come to understanding. This essay attempts to bring forth the importance of what educators can learn from one another through the suffering of experiences: the transformative effects of life, of Bildung. Largely taken, such a shift could also positively affect educator's understanding of inclusion. Keywords Bildung, predominant discourse, special education, practice, trauma, experience